Bio-analytical method development of generic formulations manufactured at IIUM Pharmaceutical manufacturing plant - Helal Uddin, A.B.M. (2017)
Generic drug is a pharmaceutical product, usually intended to be interchangeable with the innovator product, marketed after the expiry of patent or another exclusivity right. After the Hatch Waxman act 1984 expansion of the manufacturing of generic formulations has increased manifold all over the world especially in developing countries. It is required to perform bio-equivalence study for all generic solid dosage forms to ensure the quality, safety and efficacy of the drug. At IIUM pharmaceutical manufacturing plant several generic formulation project has been undertaken to be registered and marketed for local and international usage. Current study focus on the bio-analytical method development of antidiabetic and antihypertensive generic formulations manufactured at IIUM pharmaceutical manufacturing plant in order to support the bio-equivalency of the product. Amlodipine, Gliclazide and Perindopril are the generic drugs being investigated for plasma level detection in human and animal plasma. Challenge of bio-analytical method development greatly lies on cleaner sample preparation and subsequent detection at a low level to capture the drug excretion trend after administration to determine the pharmacokinetic parameters. LC MSMS and UV-Vis detection of the drugs were reported. Liquid-liquid extraction and protein precipitation technique was evaluated for the sample preparation. The recovery of gliclazide and internal standard was found between 75.31% and 104.84% respectively. Interday and intraday precision accuracy was evaluated based on the three different QC concentration namely low (L), medium (M) and high (H). The intraday precision was between 2.06 – 12.90 % and inter day precision was in the ranges of 7.27 – 10.63 % respectively for gliclazide and internal standard. It was found that the recovery of developed method varied between 88.78% - 107.04 % for perindopril and 73.93 – 79.24 % for amlodipine. It demonstrated high accuracy and precision for amlodipine and perindopril the intraday and inter day precision of perindopril were 3.14% - 12.37% and 4.4% - 9.2% respectively, while it was between 3% - 9.05% and 5.78% - 13.17% for amlodipine respectively. Methods were validated following the CDER (FDA) guideline and all the parameters were found within the acceptable range of the prescribed guideline.